THE TENTH GRADERS’ PERCEPTIONS ABOUT COLLABORATIVE LEARNING TO IMPROVE ENGLISH SPEAKING SKILLS - Lourie Maria Katiandagho; Listyani Listyani (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2019)
Collaborative learning is a method where students learn by working together to achieve a task or goal. The implementation of this method can be maximized by using games. This study aims to find out how collaborative learning with games influenced English speaking skills of the tenth-grader students, and what challenges were faced in doing collaborative learning games. The study was completed using a qualitative descriptive design and was conducted with 20 tenth-grade students at a private senior high school in Salatiga, Indonesia. To explore the students’ views on the use of the collaborative learning with games, all 20 students were asked to fill in a questionnaire and four selected students then completed a semi-structured interview. The data were then analyzed by thematic analysis. The findings revealed a positive result from the students on the use of collaborative learning activities. The study also provides some pedagogical implications and suggestions for further investigations